KEBUDAYAAN DALAM ISLAM: MENCARI MAKNA DAN HAKEKAT KEBUDAYAAN ISLAM - Mustopa Mustopa (IAIN Syekh Nurjati Cirebon, 2017)
AbstractIslam as a religion that puts reason in a very respectable position, so that Islam encourages its people to always use their minds. With reason, human has diverification from other God's creatures. By reason, humans have also reached a high culture and civilization. Therefore humans are referred as civilized and civilized beings. Thus, it is true that Islam is a religion that upholds culture and civilization. Therefore it is not surprising that Muslims have reached the golden age by being in the top position in civilization and culture. Even the classical era been a historical witness of the existence of Muslims as the most advanced people in the field of culture and civilization on earth.Keywords: Keywords: Islam, Culture, and Islamic Culture